Digital Resources for Manuscripts: Between Fragmentation and Development Prospects - Senatore, Chiara; Roberto Rosselli Del Turco; Paola Pisano (Mimesis Journal, 2024)
The path that has led to the digitization of a large part of Italy’s Cultural Heritage has been very uneven and has caused a considerable level of fragmentation in its management and delivery to the intended public. The purpose of this contribution is to briefly assess the digital resources currently available for research on manuscripts, to highlight the problem of the fragmentary nature of these resources and the ways in which attempts have been made to resolve the problem also expanding the user base, and to propose a possible way of achieving these goals based on the EVT software tool.